Building iPhone OS Accessories Use the iPhone Accessories API to Control and Monitor Devices - Maskrey, Ken.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
This book provides a serious, in-depth look at Apple$1 (Bs External Accessory framework and the iPhone Accessories API. You$1 (Bll learn how to create new, integrated solutions that combine iPhone apps with dedicated hardware. The iPhone OS Accessories API expands the opportunities for innovative iPhone developers, allowing you to control and monitor external devices, whether you$1 (Bve built them yourself or obtained them from a third party.s
What is an Accessory? -- Accessory Overview -- EAAccessory Framework -- EA Framework Design Patterns -- Project Walkthrough -- The Game Controller -- Specifying a Pong Game -- Coding a Pong Game -- Adding the Game Controller -- Improving the Design -- Apple Developer Programs -- Designing an Accessory -- Hardware Design -- Firmware -- Everything Else.
Keywords: Computer science; Computer Science; Programming Techniques